Socialization Of Tourism Awareness As An Effort To Increase The Role Of The Community In The Development Of Tourist Destinations In Batam City - Moh. Thandzir; Dailami; Tito Pratama; Haufi Sukmamedian; Wahyudi Ilham; Natal Olotua Sipayung; Rezki Alhamdi; Abd Rahmad Yusuf (PUSLITABMAS-Politeknik Pariwisata Batamc, 2026)
The Community Service Activity (PKM) with the title